2011
DOI: 10.1016/j.techfore.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Superexponential long-term trends in information technology

Abstract: Moore's Law has created a popular perception of exponential progress in information technology. But is the progress of IT really exponential? In this paper we examine long time series of data documenting progress in information technology gathered by Koh and Magee (2006). We analyze six different historical trends of progress for several technologies grouped into the following three functional tasks: information storage, information transportation (bandwidth), and information transformation (speed of computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…We broaden the system of interfunctions including the action efficiency and total amount of action in a complex system, based on a system of ordinary differential equations: (i) which leads to exponential growth with time, and (ii) establishes a power relation between the two, with measures such as the total flow of events, which is the number of computations for the CPUs and the number of transistors. Our study can also explain the origin of the observed exponential change in technology, noticed empirically by Moore [26], Kurzweil [27], Nagy et al [28], and Kelly [29]. This understanding can help describe, quantify, measure, manage, design and predict future behavior of complex systems to achieve the highest rates of self-organization to improve their quality.…”
Section: Introductionsupporting
confidence: 61%
“…We broaden the system of interfunctions including the action efficiency and total amount of action in a complex system, based on a system of ordinary differential equations: (i) which leads to exponential growth with time, and (ii) establishes a power relation between the two, with measures such as the total flow of events, which is the number of computations for the CPUs and the number of transistors. Our study can also explain the origin of the observed exponential change in technology, noticed empirically by Moore [26], Kurzweil [27], Nagy et al [28], and Kelly [29]. This understanding can help describe, quantify, measure, manage, design and predict future behavior of complex systems to achieve the highest rates of self-organization to improve their quality.…”
Section: Introductionsupporting
confidence: 61%
“…In this paper we find that the positive feedback between the least unit action and the maximum total action leads to a process of exponential growth in time of both of them and a power law relation between them characterizing developing systems and is ubiquitous in nature [27][28][29][30]. The effect of system's size on its efficiency also supports this observation [31][32][33] as do the processes of growth and efficiency in information and other technologies [34][35][36]. Development and evolution in different systems have been studied through the dynamics of complex systems in great detail, and some projections about the future of this trajectory have been made [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 72%
“…Technological progress shows signs of being super-exponential when examined across technological paradigms [86]. New computational platforms, from nano-technological modelling of neurons [87], to developments in quantum computing [88], provide justification that artificial processing might maintain its exponential growth even beyond its silicon basis.…”
Section: Biology and Digital Technology -Cooperation Or Conflict?mentioning
confidence: 99%